Hyperglycemic emergencies - epidemiological, physiopathological aspects and therapeutic management - Mittelmann, Larissa; De Araújo Gomes, Mariana; Araujo Gontijo, Joao Vitor; Ebner Salvato , Bruna; Girão Butruce Santoro, Julia; Teixeira Izidorio, Frederico; Mariana Cachola Pereira, Julia; Miranda Espírito Santo E Silva, Mariana; Carvalho Chaves, Jênifer (Seven Editora, 2023)
Diabetes mellitus (DM) corresponds to a metabolic immunity in which there is a definition of resistance1, corresponding to peripheral resistance to DM, respectively. The disease has a high prevalence and can lead to acute and numerous complications worldwide, as well as chronic; in this sense, diabetic ketoacidosis (DKA) and the hyperosmolar hyperglycemic state (HHE) correspond to the main acute complications of the disease; diagnosis and immediate treatment due to the severity of the same condition by them. In addition, both complications are called hyperglycemic emergencies, precisely because of their signs and symptoms, high blood glucose can occur in a diabetic patient. Furthermore, there are several causes of CAD and EHH; however, the main causes established in the literature are the presence of infections and the inappropriate use of insulin in patients with DM. In addition, proper patient management in these circumstances involves early administration of intravenous fluids, insulin therapy, electrolyte replacement, and recognition and treatment of precipitating causes. However, despite the existence of numerous protocols involved in the diagnosis and treatment of DKA and HHE, little has been done to prevent these complications; thus, there is an urgent need to better clarify diabetic patients about their disease and its likely complications, as well as alert them to possible warning signs, so that they can seek assistance as early as possible, reducing the likelihood of negative outcomes. DOI: https://doi.org/10.56238/tfisdwv1-044